Lumière sur Eugène Martial Simas, décorateur oublié de la Belle Époque - Constance Desanti (Les Cahiers de l'École du Louvre)
The Brasserie Mollard in Paris, the restaurant La Cigale in Nantes, Tours train station and the Créteil town hall are all “Belle Epoque” public buildings that were decorated in part by Eugène Martial Simas. This article is an introduction to the polymorphous oeuvre of Simas, who trained as a set designer, then turned to the decorative and industrial arts to exercise his fascination for new forms and forms inspired by Japanese art. Attached to classical mythology and traditional craftsmanship, Eugène Martial cleared the way for the new generation of artists that propagated its gentle utopia of a new art, present everywhere and accessible to everyone, at the turn of the twentieth century.